A pedagogy of ‘public criminology’ as a counter to marginality? Lessons for community sanctions and measures from the Pedagogy of the Oppressed - Tidmarsh, Matt (Probation journal, 2023)
As a subject of study in higher education, criminology has never been more popular; and yet, criminologists occupy an increasingly marginal position within political and media spheres. This marginalisation has arguably been to the detriment of those with lived experience of the criminal justice system, an oppressed class whose number has grown exponentially after several decades of a ‘tough on crime’ consensus on criminality. While much research focuses upon the impacts on imprisonment, an emergent literature has highlighted how individuals experience community sanctions and measures (CSM). This article utilises Paulo Freire's Pedagogy of the Oppressed to accentuate the transformative potential of teaching and learning practises within criminology, and CSM in particular. It applies his writings to the literature on ‘public criminology’, a perspective that aims to render the field more transparent, applied, evidence-based, empowering, and committed to social justice. Drawing from personal reflections as an ‘academic criminologist’ engaged in teaching and research on CSM, the article advocates for a ‘pedagogy of public criminology’ that empowers students, as future criminal justice professionals, with the skills to be public-facing, active, and critical subjects who can make a difference in the lives of individuals subject to CSM.